Disciplining sexual and reproductive behaviour of tuberculosis patients in Bangladesh: a mixed method study exploring divergent messages. Issue 2 (10th January 2022) - Barua, Mrittika; van Driel, Francien
ABSTRACT: There is scant information on the instructions provided by health workers to patients diagnosed with tuberculosis and the implications these instructions have for sexual and reproductive health and rights and tuberculosis control in Bangladesh. This paper aims to draw attention to tuberculosis control guidelines and information dissemination practices that may need to be adapted to the living situations of those with tuberculosis. Data collection took place in the Monohardi and Narsingdi Sadar sub-districts in Narsingdi and the Mirpur slum in Dhaka, Bangladesh, between December 2015 and March 2016. We present findings from an analysis of four significant documents, 45 in-depth interviews (of current and former tuberculosis patients, their family members, and health workers), and two focus group discussions with health workers. The findings show that the official guidelines and policies hardly address sexual health or rights. During the treatment period, patients received mixed and inconsistent instructions from health workers on sexual intercourse, contraception, pregnancy, and living arrangements. The messages were interpreted differently based on who delivered and received them, and different instructions were provided to women and men. The instructions were not specific to the living situations of patients and therefore led to implementation challenges. Future interventions should ensure correct and consistent messaging, and policies should be adapted to the sexual needs of those infected with the disease.